2020
DOI: 10.1515/tjb-2019-0157
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of miRNAS in patients with gestational diabetes

Abstract: BackgroundGestational diabetes mellitus (GDM), which has been identified for the first time during pregnancy and is defined as glucose intolerance of varying degrees, is one of the prediabetes states that are at risk for developing type 2 diabetes. MicroRNAs (miRNAs) are associated with pregnancy complications and are even necessary for the regulation of pancreatic development and glucose-induced insulin secretion. This study aims to investigate miRNAs expressed in maternal plasma to detect the availability as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Of the three studies, one study reported higher levels of miR-9 in the serum of Mexican women with GDM compared to controls (49). In contrast, two studies profiling miRNAs in placental tissue of Chinese women (46) and in plasma samples of Turkish women (32) reported lower expression of miR-9 in women with GDM compared to controls. Of the seven studies reporting on miR-16, three studies demonstrated higher expression in serum and plasma samples of Chinese and European women with GDM compared to controls (34,62,83).…”
Section: Qualitative Synthesis Of Studiesmentioning
confidence: 93%
See 3 more Smart Citations
“…Of the three studies, one study reported higher levels of miR-9 in the serum of Mexican women with GDM compared to controls (49). In contrast, two studies profiling miRNAs in placental tissue of Chinese women (46) and in plasma samples of Turkish women (32) reported lower expression of miR-9 in women with GDM compared to controls. Of the seven studies reporting on miR-16, three studies demonstrated higher expression in serum and plasma samples of Chinese and European women with GDM compared to controls (34,62,83).…”
Section: Qualitative Synthesis Of Studiesmentioning
confidence: 93%
“…Two studies reported on the expression of miR-142 and miR-143 during GDM. One study reported higher expression of miR-142 and miR-143 in plasma of Turkish women with GDM compared to controls (32). Stirm et al (60) reported higher expression of miR-142 and miR-143 in the whole blood of German women with GDM in the screening group, however, these findings were not validated in a larger sample.…”
Section: Qualitative Synthesis Of Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, Yoffe et al found upregulated levels of miR-223 & miR-23a in GDM patients during the first trimester of pregnancy, which might guide to develop of a non-invasive prenatal testing (NIPT) method during the first or early second trimester of pregnancy to manage GDM effectively and to prevent related risks on morphogenesis and organogenesis (1). Finally, Balci et al also reported increased miR-7-5p levels during the late second trimester of pregnancy in women with GDM (18). The key findings of recent literature on miR as GDM biomarker have been summarized in table 1.…”
Section: Expression Of Mir In Gestational Diabetesmentioning
confidence: 96%